Breakthrough infections with the omicron and delta variants of SARS-CoV-2 result in similar re-activation of vaccine-induced immunity - Søraas, Arne; Grødeland, Gunnveig; Granerud, Beathe Kiland; Ueland, Thor; Lind, Andreas; Fevang, Børre; Murphy, Sarah L.; Huse, Camilla; Nygaard, Anders Benteson; Steffensen, Anne Katrine; al-Baldawi, Huda; Holberg-Petersen, Mona; et al. (Frontiers in Immunology, 2022)
Background Results showing that sera from double vaccinated individuals have minimal neutralizing activity against Omicron have been interpreted as indicating the need for a third vaccine dose for protection. However, there is little information about early immune responses to Omicron infection in double vaccinated individuals. Methods We measured inflammatory mediators, antibodies to the SARS-CoV-2 spike and nucleocapsid proteins, and spike peptide-induced release of interferon gamma in whole blood in 51 double-vaccinated individuals infected with Omicron, in 14 infected with Delta, and in 18 healthy controls. The median time points for the first and second samples were 7 and 14 days after symptom onset, respectively. Findings Infection with Omicron or Delta led to a rapid and similar increase in antibodies to the receptor-binding domain (RBD) of Omicron protein and spike peptide-induced interferon gamma in whole blood. Both the Omicron- and the Delta-infected patients had a mild and transient increase in inflammatory parameters. Interpretation The results suggest that two vaccine doses are sufficient to mount a rapid and potent immune response upon infection in healthy individuals of with the Omicron variant. Funding The study was funded by the Oslo University Hospital, and by grants from The Coalition for Epidemic Preparedness Innovations, Research Council of Norway (no 312780, 324272), South-Eastern Norway Regional Health Authority (no 2019067, 2021071, 10357, 2021047, 33612, 2021087, 2017092), EU Horizon 2020 grant no 848099, a philantropic donation from Vivaldi Invest A/S, and The European Virus Archive Global.